The bond strengths of pit and fissure sealant to composite, to glass ionomer cement, and to compomer - Garcia, Ma. Celina U.; Lim, Rizza C.; Tumang, Heherson M. (Adviser).
The bond of pit and fissure sealant to the underlying restorative material is essential in the caries preventive role of preventive resin restorations. This study aimed to determine the bond strength of pit and fissure sealant (PFS) to composite, to glass ionomer cement (GIC), and to compomer. In the experiment, 6 assemblies each of composite-PFS-composite, GIC-PFS-GIC, and compomer-PFS-compomer were prepared. Each assembly consisted of PFS sandwiched in between two blocks of the restorative material being tested. Using a Universal Testing Machine, six samples each of the three different assemblies were subjected to shear bond strength testing. Results revealed a significant difference in the mean shear bond strengths of PFS to composite, to GIC. and to compomer at a .0001 level of significance using the Analysis of Variance. Multiple Comparison Test ranked the mean shear bond strengths of the 3 restorative materials to PFS as follows: composite-PFS-composite = compomer-PFS-compomer > GIC-PFS-GIC.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.